A methods engineering study on Baskets and Things International Corp. - Apolinario, Napoleon (College of Engineering, 1999)
Baskets & Things International Corporation is a company producing handicrafts made out of Philippine indigenous materials for export, mainly in Japan. It currently runs its production in Marikina City with a workforce of 21++. The group gathered relevant information about the company's operations and production processes. A time study has been conducted on processes of the following products : (1) 2-set sliced wood basket and (2) 7-step decorative wood ladder. It has been determined through time study that the production time standard for 2-set round sliced-wood basket and 7-step decorative wood ladder are STp=6:42.69 and STp=8:19.62 respectively. Baskets & Things operates its present system with the following major problems, which the group has identified through preliminary methods study : unsystematic plant layout, workers perform tasks where there is available space, lack of policy implementation, management's leniency in carrying out set rules, improper materials storage, finished products and/or raw materials are stored in inappropriate places, lack of systems and procedures forms not all forms are standardized and readily available. Upon proper analysis of the above stated problems, the group has arrived with several alternatives to introduce solutions to the problem. The following are the chosen alternatives and corresponding effects on the system, which the group would recommend to the management : To implement a Process Flow Layout. This would eliminate delays in production by enhancing production flow and by decreasing the distance traveled by workers from 153.3 m to 98.3 m. To implement proper (1) work hours, lunch and break times; (2) smoking limitation/areas; (3) workers' job description; and (4) workplace assignment. This would increase productivity in the workplace and worker concentration/motivation. This would also increase the level of safety in the plant and further improve working conditions in the present system. To install permanent storage places in the first and second floors of the plant. This would enhance materials handling by increasing ease of accessing inventory and mobility of materials. This would also increase work space availability. In implementing this alternative the management has to spend approximately PhP1,500 for each rack utilized for storage. To recommend standard and economical systems and procedures forms and proper inventory of forms. This would facilitate proper transactions undertaken by the management without considerable information and time loss.